Pembuatan Content Media Sosial Instagram Menggunakan Canva Untuk Promosi Objek Wisata Kampung Gelam Palembang - Della Oktaviany; Arif Prambayun; Yunita Fauzia Achmad; Ica Admirani (Pusat Riset dan Inovasi Nasional, 2023)
Kampung Gelam Palembang tourist attraction, which is located in the Pulo Kerto area, Gandus Village, Palembang, is a camping ground area which has a herbal plantation covering an area of ​​eight hectares. This community service is motivated by the occurrence of a tourism promotion business phenomenon which is carried out through social media. This phenomenon shows the realization of tourism promotion activities through social media with the aim of researchers being able to find out tourism promotion strategies through social media. This community service uses the Palembang Gelam Village tourist attraction as a place of community service. Collecting data on community service is obtained through interviews, observation, documentation with the management. The use of social media as a promotional medium can develop, raise the name of Kampung Gelam Palembang, and be able to compete with other tourist attractions in the city of Palembang and South Sumatra.